Alojzija Zupan Sosič: Teorija pripovedi: Maribor: Litera. 2017. (Knjižna zbirka Znanstvena literatura). 451 str. - Vollmaier Lubej, Janja (Slavia Centralis, 2020)
The author presents a monograph by Alojzija Zupan Sosič, entitled Theory of Narrative (2017).
Keywords: review; literary theory; narrative; Alojzija Zupan Sosič; Teorija pripovedi